Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.20546/ijcmas.2017.607.221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Stability Analysis for Yield and its Components Traits in Soybean (Glycine max L.)

Abstract: Seven soybean entries namely;(Crawford, Giza 21, Giza 22, Giza 35, Giza 82, Giza 83 and Giza 111) with different reaction for highly yielding, tolerance for salinity, water deficit conditions and resistance for diseases were evaluated under twelve environments through two years (2015, 2016 seasons), three locations (the farm of agricultural research in Mansoura city, Dakahlia Governorate, the farm of agriculture research center, Sakha station Kafr El-Sheikh governorate and the farm of national research Centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…For SCA effects, we note that the five previous promising hybrids which have excelled for heterosis over better parent and SCA effects can continue to be cultivated and evaluated for several generations under the normal and drought conditions with simple selection after each segregation generation to reach to the maximum genetic stability that can be achieved and in finally obtaining lines that are highly yielding, resistant to disease, and tolerant to salinity and water deficit under Egyptian conditions. These results were in agreement with those reported by , El-Mouhamady (2009), El-keredy et al (2003, Esmail et al (2016, Eldessouky et al (2016), Ramadan et al (2016), Khatab et al (2017), and Khatab et al (2019).…”
Section: Discussionsupporting
confidence: 92%
“…For SCA effects, we note that the five previous promising hybrids which have excelled for heterosis over better parent and SCA effects can continue to be cultivated and evaluated for several generations under the normal and drought conditions with simple selection after each segregation generation to reach to the maximum genetic stability that can be achieved and in finally obtaining lines that are highly yielding, resistant to disease, and tolerant to salinity and water deficit under Egyptian conditions. These results were in agreement with those reported by , El-Mouhamady (2009), El-keredy et al (2003, Esmail et al (2016, Eldessouky et al (2016), Ramadan et al (2016), Khatab et al (2017), and Khatab et al (2019).…”
Section: Discussionsupporting
confidence: 92%
“…On the same track, Onyia et al (2017) lectured genetic variability and rapport of some agronomic characters of rice and their assists for yield by using 12 rice entries for expansion and yield manifestation in south-eastern Nigeria and detected that the entries ITA 150,and FAROX 16 (LC)) recorded the highest stable production genotypes within two seasons of the trial. While genetic stability and heritability in the broad sense were found in seven soybean genotypes in three regions, two sowing dates and two seasons were estimated by El-Mouhamady et al (2017) who confirmed that the entries (Crawford,Giza 21,Giza 22,Giza 35,Giza 83,and Giza 111) were recorded as highly genetically stable according to the data of stability analysis under all conditions. The genetic stability that was discussed included certain traits, especially grain yield/ plant in some promising rice entries under control and water-deficit conditions pending venereal interval and the final results confirmed that the entries (IR83142-B-7-B-B, Binuhangin, IR77298-14-1-2-13, IR70215-70-CPA-3-4-1-3, and IR77298-14-1-2) recorded high genetic stability and were better stable for the final production of yielding under the two conditions over 11 years, respectively (Torres and Henry 2018).…”
Section: Introductionmentioning
confidence: 72%
“…The results of stability parameter bi may be indicated by the damaging of the genetic stability and the ambit of acclimating for these lines under various types of conditions beside, this diverse may be alteration from line to line according to the kind of this environment conditions, while the S 2 di parameter results revealed the optimum values for the highest entries for genetic stability and showed the better mean values for all studied traits under the 12 experiments, so the lines 1, 3, 4, and 5 came in the first rank for highly genetic stability under any conditions for the 12 environments, while the line numbers 2, 6, and 7 exhibited the second track in this regard (Table 13) (El-Mouhamady et al 2017). Results of R 2 showed that the lines number (1, 3, 4, and 5) were recorded highly genetically stable under all conditions particularly with better agricultural administration.…”
Section: Discussionmentioning
confidence: 88%